B cell phenotype and serum levels of interferons, BAFF, and APRIL in multisystem inflammatory syndrome in children associated with COVID-19 (MIS-C) - Adam Klocperk; Marketa Bloomfield; Zuzana Parackova; Ludovic Aillot; Jiri Fremuth; Lumir Sasek; Jan David; Filip Fencl; Aneta Skotnicova; Katerina Rejlova; Martin Magner; Ondrej Hrusak; et al. (SpringerOpen, 2023)
Abstract Background Multisystem inflammatory syndrome in children associated with COVID-19 (MIS-C) is a late complication of pediatric COVID-19, which follows weeks after the original SARS-CoV-2 infection, regardless of its severity. It is characterized by hyperinflammation, neutrophilia, lymphopenia, and activation of T cells with elevated IFN-γ. Observing the production of autoantibodies and parallels with systemic autoimmune disorders, such as systemic lupus erythematodes (SLE), we explored B cell phenotype and serum levels of type I, II, and III interferons, as well as the cytokines BAFF and APRIL in a cohort of MIS-C patients and healthy children after COVID-19. Results We documented a significant elevation of IFN-γ, but not IFN-α and IFN-λ in MIS-C patients. BAFF was elevated in MIS-C patient sera and accompanied by decreased BAFFR expression on all B cell subtypes. The proportion of plasmablasts was significantly lower in patients compared to healthy post-COVID children. We noted the pre-IVIG presence of ENA Ro60 autoantibodies in 4/35 tested MIS-C patients. Conclusions Our work shows the involvement of humoral immunity in MIS-C and hints at parallels with the pathophysiology of SLE, with autoreactive B cells driven towards autoantibody production by elevated BAFF. Graphical Abstract